The Effect of Profitability, Liquidity, and Leverage on Stock Prices in the Food and Beverage Sector Listed on the Indonesia Stock Exchange 2022-2024 - Suadnyana, I Putu Arik; Suriani, Ni Nyoman; Maharani, Ida Ayu Dinda Priyanka (Journal of Governance, Taxation and Auditing, 2026)
This study aimed to determine the effect of profitability, liquidity, and leverage on stock prices in the food and beverage sector listed on the Indonesia Stock Exchange in 2022-2024. The population used in this study was 32 companies in the food and beverage sector listed on the Indonesia Stock Exchange during the 2022-2024 period. The sampling method used in this study was purposive sampling. The sample used in this study was 16 food and beverage companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The results showed that profitability, liquidity, and leverage simultaneously had a positive effect on stock prices in the food and beverage sector listed on the Indonesia Stock Exchange during the 2022-2024 period. Profitability, proxied by Return on Equity, had a significant positive effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange during the 2022-2024 period. Liquidity, as measured by the Current Ratio, had a positive but insignificant effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in 2022-2024. Leverage, as measured by the Debt to Equity Ratio, had a significant positive effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in 2022-2024.